Evaluating Injury Risk and Gender Performance on Health- and Skill-Related Fitness Assessments. Issue 4 (April 2017) - Grier, Tyson L.; Canham-Chervak, Michelle; Bushman, Timothy T.; Anderson, Morgan K.; North, William J.; Jones, Bruce H.
Abstract : Abstract: Grier, TL, Canham-Chervak, M, Bushman, TT, Anderson, MK, North, WJ, and Jones, BH. Evaluating injury risk and gender performance on health- and skill-related fitness assessments. J Strength Cond Res 31(4): 971–980, 2017—The purpose of this analysis was to investigate the association of injury risk and gender performance on health- and skill-related fitness assessments. A survey was used to collect personal characteristics and Army Physical Fitness Test scores (2-mile run, push-ups, and sit-ups). Within the same day, 9 physical fitness assessments were performed. Percent body fat was estimated using height, weight, age, and sex. All fitness assessment data were categorized into tertiles of high, moderate and low performance. To investigate potential injury risk predicted by fitness assessment performance, injury risk ratios, odds ratios (ORs), and 95% confidence intervals (CIs) were calculated using medical record data. A total of 3, 264 soldiers completed surveys and physical fitness assessments. Tertiles of fitness performance with men and women combined showed that on an average, 14% of women and 70% of men were in the moderate- and high-performance groups. Among men, higher injury risk was independently associated with low performance on a 2-mile run (ORslow/fast = 1.51, 95% CI 1.18–1.94) and low performance on a weighted 300-yard shuttle run (ORslow/fast = 1.36, 95% CI 1.06–1.74). For women, a higher risk of injury was associated with low performance on the 2-mile run (ORslow/fast = 2.38, 95% CI 1.04–5.74). Therefore, out of the 13 fitness assessments, the 2-mile run and weighted 300-yard shuttle run can also (in addition to measuring performance) be utilized to identify soldiers or athletes who are at a higher risk of experiencing an injury.